PENGARUH ZAKAT DAN MODAL INTELEKTUAL PADA KINERJA PERBANKAN SYARIAH DI INDONESIA - Andy Passyada Salampessy (Jurnal Fokus Manajemen Bisnis, 2023)
The banking industry, especially Islamic Banking in Indonesia, experiences rapid yearly development. This development is influenced by increasing performance. This study aims to examine the effect of zakat and intellectual capital on the performance of Islamic Banking in Indonesia. The sampling technique used was the purposive sampling method. Data obtained from the annual report of Islamic Banking in Indonesia registered with The Central Bank of Republic of Indonesia and The Financial Services Authority from 2011-2020. Data analysis is carried out with validity tests, reliability tests, and hypothesis tests with the help of SPSS applications. The results showed that zakat and intellectual capital variables proved to have no effect on the performance of Islamic Banking in Indonesia for the 2011-2020 period.